2022
DOI: 10.1159/000521860
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-Interleukin-17A Monoclonal Antibody, Ixekizumab, in the Treatment of Resistant Hidradenitis Suppurativa: A Case Series

Abstract: <b><i>Introduction:</i></b> Although adalimumab is the only approved biologic for the treatment of hidradenitis suppurativa (HS), the treatment response may not be satisfactory in all patients. Recently, many other biological agents, including interleukin 17 inhibitors such as ixekizumab, have shown promise. <b><i>Case Presentations:</i></b> Five severe HS (Hurley stage III) patients resistant to conventional treatments and adalimumab for at least 3 months were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
8
0
3
Order By: Relevance
“…2 Recent studies on the pathogenesis of HS have shown that the patients with HS have imbalances in the T helper 17/interleukin (IL)-17 axis. [10][11][12] However, they may exacerbate inflammatory bowel disease or induce a new-onset condition. 13,14 One patient in our cohort had Crohn's disease, and thus, anti-IL-17 agents could not be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recent studies on the pathogenesis of HS have shown that the patients with HS have imbalances in the T helper 17/interleukin (IL)-17 axis. [10][11][12] However, they may exacerbate inflammatory bowel disease or induce a new-onset condition. 13,14 One patient in our cohort had Crohn's disease, and thus, anti-IL-17 agents could not be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the pathogenesis of HS have shown that the patients with HS have imbalances in the T helper 17/interleukin (IL)‐17 axis 10–12 . However, they may exacerbate inflammatory bowel disease or induce a new‐onset condition 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Bei 5 HS/AI-Patienten mit schwerer Manifestation der Erkrankung, die seit mindestens 3 Monaten auf konventionelle Behandlungen und Adalimumab nicht oder nicht mehr ansprachen, wurde Ixekizumab (160 mg s. c. einmalig, gefolgt von 80 mg in den Wochen 2, 4, 6, 8, 10 und 12) verabreicht 408 . Vier der 5 Patienten beobachteten eine Verbesserung der VAS- und DLQI-Werte, der Rückgang bei einem Patienten war begrenzt 408 . Es wurde kein unerwünschtes Ereignis im Zusammenhang mit Ixekizumab festgestellt.…”
Section: Therapieunclassified
“…Bimekizumab wird als subkutane Injektion verabreicht.IxekizumabIxekizumab ist ein humanisierter monoklonaler Antikörper gegen das Zytokin Interleukin-17A (IL-17A), welcher für die Therapie der HS/AI nicht zugelassen ist. Bei 5 HS/AI-Patienten mit schwerer Manifestation der Erkrankung, die seit mindestens 3 Monaten auf konventionelle Behandlungen und Adalimumab nicht oder nicht mehr ansprachen, wurde Ixekizumab (160 mg s. c. einmalig, gefolgt von 80 mg in den Wochen 2, 4, 6, 8, 10 und 12) verabreicht[408]. Vier der 5 Patienten beobachteten eine Verbesserung der VAS-und DLQI-Werte, der Rückgang bei einem Patienten war begrenzt[408].…”
unclassified
“…Esme et al reported on a case series of five patients with severe HS (Hurley stage III) who had been on adalimumab treatment for 3 months with poor results, these patients were switched to ixekizumab according to the psoriasis therapeutic schedule of administration. 77 The primary endpoint was HiSCR after 12 weeks. The secondary endpoints were DLQI and VAS.…”
Section: Miscellaneousmentioning
confidence: 99%